The theology of the land in Amos 7-9 - Thang, Robert Khua Hnin (Carlisle Langham Monographs, 2014)
In the book of Amos the language about land is used extensively, including terms and ideas such as Zion, YHWH's bringing of Israel into the land, references to various sanctuaries and places, harvest and famine, the relationship between the northern kingdom and Judah, and references to the land of other nations. However this subject of the land has never been studied as a theological topic in its own right, but only as part of other themes. This work follows a synchronic reading of Amos and employing textual, literary and historical criticism the author carries out a careful theological analysis of the land. Although the findings are set in the context of the entire book of Amos, the study focuses on chapters 7-9 to explore the topic with closer detail.
Keywords: Bible. -- Amos -- Criticism, Textual. Bible. -- Amos. Land use in the Bible